A further look at the 2004 reform of the operational framework of the ECB - Massimiliano Marzo; Paolo Zagaglia (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
This note reconsiders the impact of the reform of the operational framework of the European Central Bank that took place in March 2004. We estimate a bivariate GARCH model with the overnight rate and 1-year swap rate, where identifying restrictions are imposed on the conditional variance. Differently from previous studies, we use a measure of structural correlation to show that the 1-year swap segment has decoupled from the overnight rate as the two rates do not co-vary any longer.
Keywords: 330